Self-consistent field cluster study of the origin of hyperfine interaction and isomer shift in57mfe2o3) - Das, Tara Prasad; Kelires, Pantelis C. (My University, 1987)
We have carried out a first-principle Unrestricted Hartree-Fock (UHF) investigation of the hyperfine field, isomer shift and nuclear quadrupole interaction in Fe2O3. The cluster used in our work involved Fe+3 and its six nearest O-2 neighbours. The Madelung contribution to the potential due to the rest of the ions in the lattice was explicitly incorporated. Our results will be compared with experiment and the results of a recent investigation using an approximation (MSXαExtended Scheme) to the procedure.
Keywords: Ions; Nuclear energy